1966
DOI: 10.1111/j.1476-5381.1966.tb01905.x
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of 5‐hydroxytryptophol in Brain in Vitro

Abstract: Kveder, Iskric & Keglevic (1962) described the formation of 5-hydroxytryptophol from 5-hydroxytryptamine (5HT) in vivo in rats. The alcohol was isolated as conjugates from urine, and distinguished from 1'-N-acetyl 5-hydroxytryptamine by paper chromatography. Feldstein & Wong (1965) demonstrated the enzymatic conversion of 5HT to 5-hydroxytryptophol in rat liver. The alcohol appears also to be a major metabolite of the amine in platelets (Bartholini, Pletscher & Bruderer, 1964).The isolation of the alcohol from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

1968
1968
1981
1981

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 11 publications
(16 reference statements)
2
9
2
Order By: Relevance
“…A similar phenomenon was reported in the rat for metabolites of tyramine (Tacker et al, 1970). The above inability of ethanol to produce a reversal in the metabolism of biogenic amines in the brain is supported by reports on the effect of ethanol on 5-hydroxytryptamine metabolism in the whole rat brain (Tyce et al, 1970;Carlsson & Lindqvist, 1973) and in brain slices (Eccleston, Reading & Ritchie, 1969).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A similar phenomenon was reported in the rat for metabolites of tyramine (Tacker et al, 1970). The above inability of ethanol to produce a reversal in the metabolism of biogenic amines in the brain is supported by reports on the effect of ethanol on 5-hydroxytryptamine metabolism in the whole rat brain (Tyce et al, 1970;Carlsson & Lindqvist, 1973) and in brain slices (Eccleston, Reading & Ritchie, 1969).…”
Section: Discussionsupporting
confidence: 65%
“…The brain metabolism of ,-hydroxylated biogenic amines (noradrenaline and octopamine) have been reported by several workers (Rutledge & Jonason, 1967;Breese, Chase & Kopin, 1969a,b;Eccleston et al, 1969) and predicted by a computer simulation approach to produce mostly the alcoholic metabolites (Turner, Illingworth & Tipton, 1974). Biogenic amines with no P-hydroxyl groups, on the other hand, were reported to form mostly the acidic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In rat (Table 2) and human (Feldstein, Williamson & Tedeschi, unpublished) brain homogenates, we have found that 5-HIAA formation was moderately stimulated by NAD+ and to a lesser extent by NADP+. The quality of the NAD+ may explain the difference between our results and those obtained by Eccleston et al (1966), because enzymic activity was dependent on the source of the coenzyme (Table 3). The NAD+ used in our studies was rated greater than 99% pure by the company and had maximal activity available.…”
Section: Discussioncontrasting
confidence: 87%
“…The quality of the NAD+ may explain the difference between our results and those obtained by Eccleston et al (1966), because enzymic activity was dependent on the source of the coenzyme (Table 3). The NAD+ used in our studies was rated greater than 99% pure by the company and had maximal activity available.…”
Section: Discussioncontrasting
confidence: 56%
“…5-Hydroxytryptophol and its conjugates have been identified as normal metabolites in human urine and human and rat brain homogenates (10,11). Ethanol consumption shifts tryptophan metabolism away from the oxidation metabolite, 11, toward the reduced metabolite, V, as a result of the increased ratio of reduced to unreduced nucleotide cofactors effected by ethanol metabolism (12,13).…”
Section: Introductionmentioning
confidence: 99%